A Review of DNA Cryptography - Ling Chu; Yanqing Su; Xiangyu Yao; Peng Xu; Wenbin Liu (Intelligent Computing)
Deoxyribonucleic acid (DNA), the oldest natural storage medium, offers a highly promising mode for information computing and storage with its high information density, low maintenance costs, and the ability to do parallel processing. DNA cryptography is an emerging discipline focused on achieving information security within this new paradigm. In this paper, we first present the foundational concepts of cryptography and biological technologies involved in DNA cryptography. We then comprehensively review 2 types of DNA cryptography: pseudo-DNA cryptography and natural DNA cryptography. After summarizing and discussing the security foundations of these cryptographic methods, we highlight the main challenges relating to measurability, standard protocols, robustness, and operability. Finally, we outline future directions for DNA cryptography, hoping to facilitate the evolution of this nascent field.